The Retinoblastoma Tumor Suppressor Protein Targets Distinct General Transcription Factors To Regulate RNA Polymerase III Gene Expression - Hirsch, Heather A. (American Society for Microbiology, 2000)
The retinoblastoma protein (RB) represses RNA polymerase III transcription effectively both in vivo and in vitro. Here we demonstrate that the general transcription factors snRNA-activating protein complex (SNAP(c)) and TATA binding protein (TBP) are important for RB repression of human U6 snRNA gene transcription by RNA polymerase III. RB is associated with SNAP(c) as detected by both coimmunoprecipitation of endogenous RB with SNAP(c) and cofractionation of RB and SNAP(c) during chromatographic purification. RB also interacts with two SNAP(c) subunits, SNAP43 and SNAP50. TBP or a combination of TBP and SNAP(c) restores efficient U6 transcription from RB-treated extracts, indicating that TBP is also involved in RB regulation. In contrast, the TBP-containing complex TFIIIB restores adenovirus VAI but not human U6 transcription in RB-treated extracts, suggesting that TFIIIB is important for RB regulation of tRNA-like genes. These results suggest that different classes of RNA polymerase III-transcribed genes have distinct general transcription factor requirements for repression by RB.